Saberes e práticas populares de saúde : os processos educativos de mulheres camponesas - Teixeira, Iraí Maria de Campos (2012)
The objective of this research is to learn about the peasant women s level of understanding about health and identify their common healthcare practices, as well as their process to transfer knowledge. This study is based on the theory of Popular Education and Popular Education and Health. It adopts an amplified conception of health, which includes its social dimensions, healthcare and popular practices. It is attached to the context of the peasant women s fight for settlements, which has also been theoretically and conceptually investigated in this study. The methodological reference adopted was the participant observation, which promotes the realization of interactive activities that combines social investigation, educational work and action. Twelve female settlers from Monte Alegre settlement, State of São Paulo, were interviewed. Data was collected in the period between April 2010 and July 2011. Fifteen visits were made to the settlement, where participatory observations were made and transferred to field notes subsequently, as well as two interviews and one meeting organized by the female settlers to plan the next group conversation between the women. In order to realize the field work, a careful insertion was made in the community s workplace, in the bakery, where the women of the Women Association of Monte Alegre VI was approached. This period of relationship and sharing was fundamental for the study, because during meetings and working hours, a closest relationship to the women was developed, which favored a positive trustworthy atmosphere to the realization of interviews to satisfy the central theme around the women s comprehension of health, their personal experiences, the care practices utilized by them and its related educational process. The following data was separated for further analysis and discussion: 1) ALL OF THAT IS HEALTH and 2) THE CARE TO HEALTH AS SOCIAL PRACTICE. The data analysis shows that the women s conception of health is a combination of health and society, and takes in consideration biological, psychic, emotional aspects of health, as well as socio-economic. The data points to health care practices: the multiprofessional assistance offered by health services, the production and utilization of homemade medication, the partnership, the dialogue, the active listening and the social mobilizations. It was found that agrarian work and gender oppression were aspects that influenced the female peasant s health practices. The educational processes related to health care practices are the ones found in familiar, professional, communitarian relationship as well as the ones available through different medias and past social movement s experiences. The female settlers make themselves aware of health care issues through dialogue, researching books and magazines, studying, consulting with professionals and by learning from the attempting of diverse practices. Consequently, the peasant women are able to assess the best practices of health care, and maintain the process of knowledge transfer, based on which past social experiences are considered more adequate. Educational processes are also present during the preparation of women and men for agrarian work, as well as work division based on gender.